Attenuation curves of neutrons from 400 to 550 Mev/u for Ca, Kr, Sn, and U ions in concrete on a graphite target for the design of shielding for the RAON in-flight fragment facility in Korea - Lee, Eunjoong; Kim, Junhyeok; Kim, Giyoon; Kim, Jinhwan; Park, Kyeongjin; Cho, Gyuseong (Nuclear engineering and technology, 2019)
Rare isotope beam facilities require shielding data in early stage of their design. There is much less shielding data on neutrons from the reactions between heavy ion beams and matter than the data on neutrons produced by protons. The purpose of the present work is to produce and thus increase the amount of shielding data on neutrons generated by high-energy heavy ion beams based on the RAON in-flight fragment facility. Calculations were performed with the computational Monte Carlo codes PHITS and MCNPX. The secondary neutron source terms were evaluated at 550 MeV/u for Ca, Kr, and Sn and at 400 MeV/u for U ions on a graphite target. Source terms and attenuation lengths were obtained by fitting the ambient dose equivalent inside an ordinary concrete shield. Keywords: Heavy ion accelerator, Shielding data, Neutron attenuation, Monte Carlo